Silica Boron Sulfonic Acid as Heterogeneous and Highly Efficient Solid Acid Catalyst For the Preparation of Hantzsch 1,4-dihydropyridines Under Solvent-Free - sami sajjadifar; Pegah Masoudi (Journal of Sciences, Islamic Republic of Iran)
Silica boron sulfonic acid [SiO2–B(OSO3H)3] as an inexpensive, reusable, and Lewis and Brønsted acid catalyst was successfully synthesized, and used for the one-pot three-components synthesis of biologically active substituted Hantzsch 1,4-dihydropyridine derivatives  in the absence of solvent at 90ºC. Silica boron sulfonic acid is attractive and efficient, because it plays in two role as a Lewis acid (by boron atom) and also as a Brønsted acid (by OSO3H group), which can have a  better effect in reaction. The reaction was carried out under solvent-free and mild conditions. Silica boron sulfonic acid can be recovered and reused for at least five consecutive runs.